2013
DOI: 10.1105/tpc.113.113324
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome b5 Reductase Encoded byCBR1Is Essential for a Functional Male Gametophyte inArabidopsis   

Abstract: In all eukaryotes, NADH:cytochrome b5 reductase provides electrons, via cytochrome b5, for a range of biochemical reactions in cellular metabolism, including for fatty acid desaturation in the endoplasmic reticulum. Studies in mammals, yeast, and in vitro plant systems have shown that cytochrome b5 can, at least in some circumstances, also accept electrons from NADPH:cytochrome P450 reductase, potentially allowing for redundancy in reductase function. Here, we report characterization of three T-DNA insertional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 71 publications
2
44
1
Order By: Relevance
“…We selected NCR2 as the representative target gene of Cre-miR910 to determine the function of Cre-miR910 since degradome sequencing date revealed that NCR2 is Cre-miR910 target. NCR (or ATR in Arabidopsis ) is a membrane-bound flavoprotein and transfers reducing equivalents from NADPH to diverse P450 monooxygenases that participate in a broad range of reactions in plants, including biosynthesis of secondary metabolites, fatty acids, lipids, defense-related chemicals, and plant hormones505152. In Arabidopsis , the expression of NCR ( ATR2 ) was induced by wounding, high visible light, fungal elicitors, and UV light51.…”
Section: Discussionmentioning
confidence: 99%
“…We selected NCR2 as the representative target gene of Cre-miR910 to determine the function of Cre-miR910 since degradome sequencing date revealed that NCR2 is Cre-miR910 target. NCR (or ATR in Arabidopsis ) is a membrane-bound flavoprotein and transfers reducing equivalents from NADPH to diverse P450 monooxygenases that participate in a broad range of reactions in plants, including biosynthesis of secondary metabolites, fatty acids, lipids, defense-related chemicals, and plant hormones505152. In Arabidopsis , the expression of NCR ( ATR2 ) was induced by wounding, high visible light, fungal elicitors, and UV light51.…”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome b5 reductase (CBR) mediates electron transfer from NADH to cytochrome b5. Arabidopsis contains two CBR isoforms, CBR1 and CBR2, which localize to the ER membrane and mitochondrial inner membrane, respectively (Heazlewood et al, 2004;Kumar et al, 2006;Wayne et al, 2013). CBR1 has a key role in fatty acid desaturation in the ER membrane by transferring electrons from NADH to the heme group of cytochrome b5.…”
Section: Introductionmentioning
confidence: 99%
“…Cytochrome b5 then transfers the electrons to fatty acids desaturase 2 (FAD2) and fatty acids desaturase 3 (FAD3), which introduce double bonds into fatty acids. It has been reported that the cbr1-2 mutant plants have reduced levels of unsaturated fatty acids (particularly 18:3) in seeds (Kumar et al, 2006;Wayne et al, 2013), and that CBR1 has a crucial role in the normal functioning of male gametophytes (Wayne et al, 2013). Thus, CBR1 is a key factor in energy transfer to cellular processes that require energy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Arabidopsis has two genes coding for CYTOCHROME B5 REDUCTASE (CBR) proteins. CBR1 is located at the membrane of the endoplasmic reticulum but is mainly involved in electron transport for the biosynthesis of polyunsaturated fatty acids, whereas CBR2 is in the mitochondrial membrane, and there is no evidence yet that it could take part in the endoplasmic reticulum electron transport system (Wayne et al, 2013).…”
mentioning
confidence: 99%